Analysis of the impact of immobilisation‑induced hypodynamia on hip‑joint range of motion - Dovgan , R.R.; Masna , Z.Z. (Морфологія / Morphologia / Morfologìâ, 2025)
Relevance. A sedentary lifestyle is nowadays among the global medico‑social problems which, together with worldwide ecological changes caused by numerous technogenic catastrophes, military actions, everyday environmental pollution and infectious epidemics, lead to a rapid rise in morbidity irrespective of residence, age, sex or social status. Aim. To study the effect of prolonged immobilisation of the sacropelvic region and hind limbs of the rat on the functional capacity of the hip joints. Methods. The study included 25 mature male outbred white rats aged 3–3.5 months and weighing 180–200 g. Animals were divided into a control group (5 animals) and an experimental group (20 animals). Forced hypodynamia was modelled by immobilising the sacropelvic region and hind limbs with a plaster cast analogous to a coxite cast reinforced with wire, completely restricting movements in the hip and knee joints. Observation periods were 4 and 6 weeks after cast application. Passive range of motion was re‑evaluated in all animals 2 weeks after cast removal. Results and conclusion. With the hind limb initially positioned perpendicular to the body axis, passive hip flexion and extension in intact rats were both 90°. After prolonged immobilisation the hip range of motion decreased compared with normal. In all experimental groups the flexion angle remained higher on the left side, while the extension angle showed varying asymmetry. In the majority of animals, both right and left, the extension angle remained significantly greater than the flexion angle; the only exception were animals assessed 2 weeks after 4‑week immobilisation, in whom flexion and extension values differed insignificantly and were closest to normal. The study showed that after 6 weeks of immobilisation the hip‑joint flexion angle decreased by more than half (51–57 %) compared with normal, whereas the extension angle decreased by only 9–10 %. The changes developing after 4 and 6 weeks of forced immobilisation were reversible, as evidenced by near‑normal values 2 weeks after 4‑week immobilisation and marked recovery 2 weeks after 6‑week immobilisation. The duration of the recovery period was proportional to the duration of immobilisation.